Brainiac Caspases: Beyond the Wall of Apoptosis - Espinosa-Oliva, Ana María; García-Revilla, Juan; Alonso-Bellido, Isabel María; Burguillos, Miguel Angel (Frontiers in Cellular Neuroscience, 2019)
For the last two decades, caspases, a family of cysteine-aspartic proteases, have evolved from being considered solely as regulators of apoptosis or inflammation to having a wider range of functions. In this mini review, we focus on the most recent “non-apoptotic” roles of caspases in the CNS, particularly in neurons, astrocytes and oligodendrocytes. Non-apoptotic caspase functions in microglia have already been reviewed extensively elsewhere. Here we discuss the involvement of caspases in the activation of the inflammasome, autophagy, and non-apoptotic forms of cell death such as necroptosis and pyroptosis. Also, we review the involvement of caspases in synapses and the processing of aggregates key to neurodegenerative diseases such as Parkinson’s, Alzheimer’s and Huntington’s diseases. Likewise, we mention the recently described involvement of caspases in mitochondrial biogenesis, which is a function independent of the enzymatic activity. We conclude discussing the relevance that “new” functions of caspases have in the CNS and the future of this field of research.